2015
DOI: 10.1007/978-3-319-16345-1_5
|View full text |Cite
|
Sign up to set email alerts
|

Historical and Epistemological Perspectives on What Horizontal Gene Transfer Mechanisms Contribute to Our Understanding of Evolution

Abstract: Since the 1990s, results coming in from molecular phylogenetics necessitate us to recognize that Horizontal Gene Transfer (HGT) occurs massively across all three domains of life. Nonetheless, many of the mechanisms whereby genes can become transferred laterally have been known from the early twentieth century onward. The temporal discrepancy between the first historical observations of the processes, and the rather recent general acceptance of the documented data, poses an interesting epistemological conundrum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 191 publications
(176 reference statements)
0
9
0
Order By: Relevance
“…During their lytic cycle [68], when bacteriophages destroy their host, they accidentally package bacterial genes from their host and transmit these to recipient bacteria upon infection [69][70][71].…”
Section: Phage-mediated Transductionmentioning
confidence: 99%
See 2 more Smart Citations
“…During their lytic cycle [68], when bacteriophages destroy their host, they accidentally package bacterial genes from their host and transmit these to recipient bacteria upon infection [69][70][71].…”
Section: Phage-mediated Transductionmentioning
confidence: 99%
“…Research has shown that bacterial antibiotic resistance [124] was acquired by horizontal gene transfer [71] and horizontal gene transfer has been argued to have facilitated the evolution of the major metabolic pathways that enable prokaryotes to survive [125].…”
Section: Lateral Gene Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…Symbiosis research also progressed from within the biomedical and bacteriological sciences where bacteria became understood as parasitic agents of disease. Ferdinand Cohn published a first systematic classification of bacteria in 1872; in 1876, Robert Koch associated the anthrax bacterium with the Anthrax disease ('Milzbrand-Krankheit') in cows; Pasteur's work on the germ theory of disease was read before the French Academy of Science in 1878; and Charles Louise Alphonse Laveran, the discoverer of the malaria parasite, was one of the first to, in 1880, recognize parasitic protozoa as causative agents of disease (Gontier, 2015b).…”
Section: Symbiosis In All Animals Plants and Protists And Its Signimentioning
confidence: 99%
“…Beijerinck, another student of de Bary, also found Rhizobia, nitrogen-fixing, symbiotic bacteria present in the roots of legumes, and he was the first to point out their importance for agriculture (because rhizobia-rich roots and soil makes for fertile soil). Beijerinck is considered one of the founders of virology, and in nineteenth century academic circles, also de Bary (1861) was mostly known for his studies on plant diseases and for reporting on the life cycle of the fungus Phytophthora infestans that is parasitic on potatoes thereby causing potato blight (Gontier, 2015b).…”
Section: Symbiosis In All Animals Plants and Protists And Its Signimentioning
confidence: 99%